Drosophila LAR regulates R1-R6 and R7 target specificity in the visual system. - Clandinin, T.R.; Lee, C.H.; Herman, T.; Lee, R.C.; Yang, A.Y.; Ovasapyan, S.; Zipursky, S.L. (Neuron, 2001)
Different classes of photoreceptor neurons (R cells) in the Drosophila compound eye connect to specific targets in the optic lobe. Using a behavioral screen, we identified LAR, a receptor tyrosine phosphatase, as being required for R cell target specificity. In LAR mutant mosaic eyes, R1-R6 cells target to the lamina correctly, but fail to choose the correct pattern of target neurons. Although mutant R7 axons initially project to the correct layer of the medulla, they retract into inappropriate layers. Using single cell mosaics, we demonstrate that LAR controls targeting of R1-R6 and R7 in a cell-autonomous fashion. The phenotypes of LAR mutant R cells are strikingly similar to those seen in N-cadherin mutants.